The total energy usage in block a students residential hall (DPP) TM, UUM using energy audit - Mohd Zulkiflee, Nik Fazilah; Ibrahim, Jafni Azhan (2015)
Nowadays, people are more aware of energy efficiency, energy use in buildings.The energy audit was a through examination of the use and waste of energy in a building.My studied is about energy audit. Energy audit is also very important to know the amount of energy used in a building. In energy audit I studied about the total of light, the light energy is used and the number of bills to be paid.The present article on energy studies conducted in the fluorescent lights in Block A DPP TM.In this study, energy audit and use data collected in all places, in block A.There are many of these studies the use of waste energy used by the students in the building blocks A DPP TM.This proposal discusses about the savings made to avoid wastage.